The personal liability of directors in terms of section 424 of the Companies Act - does it provide an adequate remedy? - Rose-Innes, Leslie Andrew (Department of Commercial Law, 2024)
Companies are part of the very fabric of the modern commercial world. Very often business ventures are embarked on by a company rather than by the individual shareholders and investors in their own name. The fundamental attribute of corporate personality, well established since the decision in Salomon v Salomon and Company almost a century ago, is that a company is a legal entity- distinct from its members. The separate legal personality of a company and the limited nature of a shareholder's liability afford a measure of protection against personal liability being incurred by those who invest in a company as a shareholder or who are involved in managing a company as a director. Ordinarily the members and directors of a company will not be liable for the company's debts and liabilities. At times however these characteristics of a separate corporate personality and limited liability provide a shield behind which the unscrupulous seek to hide. It is part of commercial life that the business of some companies is conducted in an unlawful or irresponsible manner. This often results in insolvency and occasions loss to others. In certain circumstances the law provides for personal liability on the part of those responsible for such misconduct. It is necessary that appropriate legal remedies should exist.